Leptin and environmental temperature as determinants of bone marrow adiposity in female mice - Turner, Russell T.; Nesser, Kira L.; Philbrick, Kenneth A.; Wong, Carmen P.; Olson, Dawn A.; Branscum, Adam J.; Iwaniec, Urszula T. (Frontiers in Endocrinology, 2022)
Bone marrow adipose tissue (BMAT) levels are higher in distal femur metaphysis of female mice housed at thermoneutral (32°C) than in mice housed at 22°C, as are abdominal white adipose tissue (WAT) mass, and serum leptin levels. We performed two experiments to explore the role of increased leptin in temperature-enhanced accrual of BMAT. First, we supplemented 6-week-old female C57BL/6J (B6) mice with leptin for 2 weeks at 10 µg/d using a subcutaneously implanted osmotic pump. Controls consisted of ad libitum (ad lib) fed mice and mice pair fed to match food intake of leptin-supplemented mice. The mice were maintained at 32°C for the duration of treatment. At necropsy, serum leptin in leptin-supplemented mice did not differ from ad lib mice, suggesting suppression of endogenous leptin production. In support, Ucp1 expression in BAT, percent body fat, and abdominal WAT mass were lower in leptin-supplemented mice. Leptin-supplemented mice also had lower BMAT and higher bone formation in distal femur metaphysis compared to the ad lib group, changes not replicated by pair-feeding. In the second experiment, BMAT response was evaluated in 6-week-old female B6 wild type (WT), leptin-deficient ob/ob and leptin-treated (0.3 μg/d) ob/ob mice housed at 32°C for the 2-week duration of the treatment. Compared to mice sacrificed at baseline (22°C), BMAT increased in ob/ob mice as well as WT mice, indicating a leptin independent response to increased temperature. However, infusion of ob/ob mice with leptin, at a dose rate having negligible effects on either energy metabolism or serum leptin levels, attenuated the increase in BMAT. In summary, increased housing temperature and increased leptin have independent but opposing effects on BMAT in mice.